Women geographers and the International Geographical Union - Joos Droogleever Fortuijn (Boletín de la Asociación de Geógrafos Españoles)
This article reports the under representation of women in the discipline of geography in the world and focuses on the position of women in the global geography community of the International Geographical Union IGU. First, it gives an overview of the underrepresentation of women in geography in different parts of the world, demonstrating that women are particularly underrepresented in positions of power and prestige. Second, it summarizes factors that explain the underrepresentation of women in geography. Finally, it analyzes the position of women in the governance of the IGU. It concludes that women geographers are still underrepresented in the IGU in the same way as in geography departments all over the world. The participation of women in the governance of the IGU reflects the gendered nature of subdisciplines in geography as an integrative natural sciences-social sciences-humanities discipline, with a higher share of female representation in human geography than in physical and technical subdisciplines. Female representation is more often from high-income countries in Europe, North-America and Oceania and from Latin-America than from Asia and Africa.